Hakim Mohammad Saeed Qomi, an Unknown Poet and Physician of the Safavid Era - Sayyed Hossain Sayyed Mousavi; Vahideh Fakhar Noghani; Mahboobeh Farkhondehzadeh (Journal of Research on History of Medicine, 2023)
The history of medicine during the Safavid era (1736-1501 AD) was accompanied by changes; compared to previous periods, it had a lower position. However, the presence of prominent physicians who were famous in various scientific fields caused the knowledge of pharmacology and pharmaceutics to shine so much so that the period was known as the Golden Age of pharmaceutics. Mohammad Saeed Qomi was a physician, pharmacist, and philosopher of the Safavid era who remained unknown despite his fame and important texts. The present research, performed in a descriptive-analytical manner and relying on the resources of libraries, is an attempt to identify and introduce this physician’s medical texts and his scientific life. The findings of this study indicate that hakim Mohammad Saeed Qomi, holding the title of “the Little Sage”, was one of the thinkers of the tenth century AH. He was the private physician of Safavid Shah Abbas II (1632-1666 AD). He was brought up in a scholarly family, where medicine and writing poetry were hereditary. The surviving treatises of this anonymous physician show his knowledge and approach to medical science, pharmacy, and related fields, such as anatomy. Mohammad Saeed’s medical masterpiece is called “Anatomy of the Bones of the Head and Upper Jaw”, considered the first text in the field of anatomy in the Safavid era.